Impact of Green Bonds on Firm's Valuation - Jormalainen, Antti (My University, 2020)
Among all the previous and current market-based solutions, green bonds have created one of the most potential market to channel funds to various investment projects. The main purpose of this thesis is to investigate whether the green bonds are priced lower than ordinary ones and how this would impact the fundamental value of the company through valuation methods. This thesis is focusing on rather new and interesting subject because green bonds and its markets have been studied since the inception of the first green bond in 2007 and even more widely when volumes have grown rapidly. Prior studies have concluded that the green bonds are priced more cheaply than conventional ones and the market has similar risk compared to the traditional bond market. Even though previous findings indicate different coefficient and level of significant degrees for the results, they are in the line with each other indicating the premium of green bonds can be investigated. This study finds that green bonds are little bit cheaper than conventional bonds with 0,60-0,84% premium in the studied data sample during 2013-2020. Although the green bond issuance is associated with other respective costs such as third-party assessment and certification, these costs do not exceed the available pricing advantage according to the findings. This study also investigates how the achieved premium from green bond issuance will result in cost of debt and therefore impact the valuation of a company by using the traditional DCF valuation model. Results of this thesis indicate that there are clear differences in how the fundamental value of a company grows depending on its capital structure if the cost of debt decreases by the premium of green bonds. According to the CAR tests of a company stock price that issued a green bond, shows that not every time windows have statistically significant abnormal returns, but the shortest time window [−5,5] indicates statistically significant excess returns (4,18%) during the green bond issuance.
Keywords: valuation; capital costs; company valuation; bonds; cash flow; climate changes; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance